Pendekatan Psikoanalisis Terhadap Film Master and Commander - Elve Oktafiyani (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2008)
Movie and psychoanalysis have similar characteristic. Movie creation as an art form is the process of emerging unconscious impulse and that process is the objects in psychoanalysis. Thecharacters, all of them are male in the film Master and Commander: The Far Side of The World, havethe most primitive unconscious impulse. Those impulse then expressed in many constructive and destructive form. By applying psychoanalysis on the film, the process of conducting the unconscious impulse can be explicitly described.